2011
DOI: 10.2337/dc11-0102
|View full text |Cite
|
Sign up to set email alerts
|

Continued Reduction in the Prevalence of Retinopathy in Adolescents With Type 1 Diabetes

Abstract: OBJECTIVETo examine trends in microvascular complications in adolescents with type 1 diabetes between 1990 and 2009 in Sydney, Australia.RESEARCH DESIGN AND METHODSWe used analysis of complications in 1,604 adolescents (54% female, aged 12–20 years, median duration 8.6 years), stratified by four time periods using Generalized Estimation Equations as follows: T1 (1990–1994), T2 (1995–1999), T3 (2000–2004), and T4 (2005–2009). Early retinopathy was detected using seven-field fundal photography, albumin excretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 23 publications
12
143
2
1
Order By: Relevance
“…Globally, as a consequence of the DCCT and UKPDS studies, the targets for glycaemic control have been tightened and retinopathy rates have begun to fall [21,22]. The HbA1c levels in the present cross-sectional report were not dissimilar to those found at present in many routine diabetes clinics in westernised countries [19,21,22]. How do the results of the present report compare with previous results from Ethiopia and other African countries?…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Globally, as a consequence of the DCCT and UKPDS studies, the targets for glycaemic control have been tightened and retinopathy rates have begun to fall [21,22]. The HbA1c levels in the present cross-sectional report were not dissimilar to those found at present in many routine diabetes clinics in westernised countries [19,21,22]. How do the results of the present report compare with previous results from Ethiopia and other African countries?…”
Section: Discussionsupporting
confidence: 46%
“…Although the average HbA1c levels were above the goal of ≤ 7.0% [≤ 53 mmol/mol], there was no significant difference between the glycaemic control of the urban and rural T1DM groups, despite the specific difficulties of insulin storage and regular blood glucose monitoring for the rural patients. Globally, as a consequence of the DCCT and UKPDS studies, the targets for glycaemic control have been tightened and retinopathy rates have begun to fall [21,22]. The HbA1c levels in the present cross-sectional report were not dissimilar to those found at present in many routine diabetes clinics in westernised countries [19,21,22].…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…141,142 There are limited data in youth with adolescents with T2DM, but these data suggest similar retinal abnormalities are developing. 143,144 Factors influencing retinopathy in children with T1DM include vitamin D deficiency, 145 BP, 146 duration of disease, 147 and glucose control. 148, 149 The prevalence appears to be declining in both children 150 and adults, 138 possibly related to more intensive treatment.…”
Section: Maahs Et Al Cvd Risk Factors In Youth With Diabetes Mellitusmentioning
confidence: 99%
“…Diabetic retinopathy is also associated with mortality and cardiovascular disease incidence in diabetes [2]. Prospective studies identified poor glycemic control, duration of diabetes and blood pressure as most important risk factors for development of retinopathy [3][4][5][6][7]. Retinopathy and nephropathy are most important microvascular complications in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%